The grand slam Bobby Jones, America, and the story of golf - Frost, Mark 1953- (Hyperion, 2004)
Presents a study of the life and career of golf icon Bobby Jones, focusing on his accomplishment of winning four major golfing championships during the sumer of 1930 and his sudden retirement from competition at the age of twenty-eight.